Diversity of the Terrestrial Molluscs of an Urban Secondary Forest: The National Center for Floristry (NCF) of Abidjan, Côte d’Ivoire - Jerome, N’dri Kouassi; Clair, Amani N'dri Saint; Mamadou, Karamoko; Atcho, Otchoumou (European Scientific Journal, ESJ, 2019)
The diversity of terrestrial Molluscs was studied in the National Center for Floristry (NCF) located at the University Felix Houphouet Boigny of Abidjan (Côte d’Ivoire) by combining the direct method and method of sampling litter. A total of 2626 individuals, belonging to 22 species and six families, were harvested from the 15 plots of the study area. Species richness ranges from eight to 21 species with an average of 12.66 ± 3.73. It was dominated by Subulinidae (50%) which are herbivores, and Streptaxidae (22.73%) which are carnivorous. Each plot yielded between 65 and 392 individuals (mean 175.06 ± 77.54). Numerical abundance was dominated respectively by Archachatina ventricosa with 23.61% (620 specimens), Limmicolaria flammea with 21.36% (561 specimens), and Achatina fulica with 16.60% (436 specimens). Based on the importance of the diversity of Molluscs, steps must be taken towards a better management policy for this center because these species has already been threatened by human activities.